Upaya Meningkatkan Kemampuan Guru Dalam Menyiapkan Media Pembelajaran Serbaneka Melalui Bimbingan Kelompok di SDN 195/X Sungai Jambat Semester Genap Tahun Ajaran 2021/2022 - Zainal Zainal (Journal on Education, 2023)
This research aims to improve teachers' abilities in preparing various learning media through group guidance at SDN 195/X Sungai Jambat even semester of the 2021/2022 academic year. This research is a school action research which consists of two cycles. This research was conducted at SDN 195/X Sungai Jambat in the even semester of the 2021/2022 school year with 8 teacher research subjects. Data collection techniques using observation, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that group guidance can improve teachers' abilities in making various learning media at SDN 195/X Sungai Jambat even semester of the 2021/2022 academic year.